(untitled) (Journal of Economic Research & Business Administration, 2015)
In this article were considered a few problems concerning rating system which are used in world practice, also in his article we tried to show in example form the meaning of CAMEL rating system. We know that demand for rating products is high, because it is a real analytical implement which gives us an opportunity to determine a financial position or situation of bank and other financial organizations. Rating is very important in choosing a business partner, in this way were offered some systems which can be used in practice.